Characterization of CXE genes in pineapple and their aroma-related expression during fruit ripening - Xu, Wenxin; Li, Tangxiu; Wu, Jing; Wang, You; Feng, Junting; Luan, Aiping; Carzorel, Okandze Poho Pérol; He, Shuqiang; He, Junhu; Chen, Chengjie; Ma, Wuqiang (Frontiers in Plant Science, 2025)
Carboxylesterases (CXEs) are ester hydrolyzing enzymes closely associated with the degradation of volatile esters and aroma release in fruit. Pineapple possesses a strong, ester-rich aroma, yet its CXE gene family has not been characterized. Here, we performed a genome-wide identification and analysis of the pineapple CXE family, detected 20 members, and pinpointed AcCXE4 and AcCXE7 as key negative regulators of aroma accumulation and prime candidates for aroma-oriented breeding. Phylogenetic comparison with CXEs from Arabidopsis, tomato, strawberry, Nanguo pear, and peach resolved five clades, in which AcCXE4 grouped with PuCXE15, a reported aroma-related gene in Nanguo pear, while AcCXE7 clustered with tomato SlCXE1 and AcCXE3 with apple MdCXE1, suggesting these members participate in ester metabolism in pineapple and are potential contributors to fruit-aroma formation. Besides, although AcCXE13 and AcCXE20 show conserved gene structure and sequence, their exon numbers and motif architectures differ from other AcCXEs, implying functional specialization. Comparative genomics indicated that family expansion in pineapple was driven primarily by tandem duplication and large segmental duplication. Integrating cis-regulatory element profiling, transcriptome analyses, and experimental validation, we found that most AcCXEs are likely responsive to light and hormone signaling (including the jasmonate pathway) and to abiotic stress cues. Several AcCXE genes exhibited decreasing expression across cultivars, tissues, and developmental stages, showing negative correlations with aroma accumulation, with AcCXE4 and AcCXE7 displaying the strongest association with pineapple aroma formation. Collectively, this work systematically defines the pineapple CXE family and highlights priority targets to inform molecular improvement of fruit aroma.